Pemecah Masalah Dan Pengambilan Keputusan Pada J&E Express Tanasira - Chintya Ones Charli; Tiara; Rani Sarmila Putri; Wilya Saric (Jurnal Ekonomi dan Bisnis Digital, 2024)
Currently, the development of the delivery service industry is progressing quite rapidly. The era of globalization requires humans to have high mobility. Since the start of the free market in Indonesia, the flow of trade in goods or services has become unlimited. The need for goods delivery services is increasing to meet people's needs. The existence of goods delivery service providers has a strategic role in improving the performance of the flow of goods to and from a region. The main role of goods delivery service providers is as a means of transporting goods, both over short distances (inside the city) and long distances (outside the city). The quality of goods delivery services provided is closely related to customer satisfaction. The better the quality of the goods delivery service, the higher the satisfaction felt by customers, so that it gives encouragement to customers to establish strong ties with the company. One of the challenges facing competition between goods delivery service providers is getting tighter due to the emergence of Ecommerce along with the addition of new goods delivery service providers. So in facing business competition, companies must be more competitive and provide the best services, to achieve customer satisfaction which is an important factor for creating loyalty.